2020
DOI: 10.1016/j.ebiom.2020.102661
|View full text |Cite
|
Sign up to set email alerts
|

Anti-fibrotic effect of decorin in peritoneal dialysis and PD-associated peritonitis

Abstract: Background: Progressive peritoneal fibrosis is a common complication in patients on long-term peritoneal dialysis (PD). PD-associated peritonitis is a major exacerbating factor. We investigated the anti-fibrotic properties of decorin secreted by peritoneal mesothelial cells. Methods: Dialysate decorin level in stable PD patients and those with peritonitis was measured. In vitro experiments were conducted to investigate the effect of decorin in fibrotic response in human peritoneal mesothelial cells (HPMC). Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Among the top 5 DEGs were DCN, PRG4, OGN, ITGA8, and ASPN, all of which are involved in mediating cell–cell interactions, ECM formation, and cell migration. Importantly, ECM proteins are known to function via PI3K/GSK3 signaling, including ITGA8 [ 55 ], DCN [ 67 , 68 ], and OGN [ 69 ], identified as top DEG’s, and ITGA8 and collagen subunits [ 56 , 57 ] identified as part of the PI3K/GSK3 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Among the top 5 DEGs were DCN, PRG4, OGN, ITGA8, and ASPN, all of which are involved in mediating cell–cell interactions, ECM formation, and cell migration. Importantly, ECM proteins are known to function via PI3K/GSK3 signaling, including ITGA8 [ 55 ], DCN [ 67 , 68 ], and OGN [ 69 ], identified as top DEG’s, and ITGA8 and collagen subunits [ 56 , 57 ] identified as part of the PI3K/GSK3 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that the deposition of fibronectin is repressed by decorin when HPMC were unveiled to peritoneal dialysis fluid. This effect was carried out by the downregulation of TGF-β1 and enhanced phosphorylation of glycogen synthase kinase 3 beta (GSK-3β) [22] .…”
Section: Justification Of Hypothesismentioning
confidence: 99%
“…We hypothesized that decreased decorin might contribute to the pathogenesis of epidural fibrosis and epidural adhesions. A variety of researches employing recombinant decorin or decorin gene therapy have demonstrated that decorin has anti-fibrosis activity in scar formation or fibrosis models in many organs ( Li et al, 2004 ; Jang et al, 2016 ; Chouhan et al, 2019 ; Cianfarani et al, 2019 ; Jiang et al, 2020 ). Chouhan et al ( 2019 ) synthesized a hydrogel that can sustain the release of decorin and significantly inhibit corneal scar formation.…”
Section: Introductionmentioning
confidence: 99%